Antibodies to berne virus in horses and other animals - Weiss, M. (Vet Microbiol, 1984)
After inoculation into 2 foals, Berne virus induced neutralizing antibody, but did not cause clinical symptoms. In a horizontal study of seropositive mares and their offspring, a decline of maternal antibodies and a sudden synchronous seroconversion in all foals were observed, again without clinical symptoms. The virus is widespread in the Swiss horse population and has been so during the last decade; rises in antibody titers were noted in 9% of paired sera sampled at random. Positive reactions were also obtained in serum neutralization tests and ELISA using small numbers of horse sera from Germany, France and the U.S.A. The results of neutralization tests and ELISA were correlated in 83% of random samples tested; 13% were neutralization-positive and ELISA-negative and in 4% the inverse was observed. Neutralizing activity was found in the sera of other ungulates (cattle, goat, sheep and pig), laboratory rabbits and 2 species of wild mice (Clethrionomys glareolus and Apodemus sylvaticus). Inconclusive results were obtained with feline and human sera; those from dogs and foxes (Vulpes vulpes) were consistently negative. The probable occurrence of antigenic variants in Berne-type viruses is discussed.